Integrative analysis of reference epigenomes in 20 rice varieties - Lun Zhao (Nature Portfolio, 2020)
Comprehensive epigenomic maps of various rice varieties are still unavailable. Here, the authors report the development of eChIP as a fast and low-input upgrade of regular plant ChIP-seq protocol for epigenome analysis of 20 rice varieties and annotate over 80% of the genome with different epigenome properties for transcriptional regulation.